Biotechnology and Biomaterial-Based Therapeutic Strategies for Age-Related Macular Degeneration. Part I: Biomaterials-Based Drug Delivery Devices - Jemni-Damer, Nahla; Guedan-Duran, Atocha; Fuentes-Andion, María; Serrano-Bengoechea, Nora; Alfageme-Lopez, Nuria; Armada-Maresca, Felix; Guinea, Gustavo V.; Pérez-Rigueiro, José; Rojo, Francisco; Gonzalez-Nieto, Daniel; Kaplan, David L.; Panetsos, Fivos (Frontiers in Bioengineering and Biotechnology, 2020)
Age-related Macular Degeneration (AMD) is an up-to-date untreatable chronic neurodegenerative eye disease of multifactorial origin, and the main causes of blindness in over 65 years old people. It is characterized by a slow progression and the presence of a multitude of factors, highlighting those related to diet, genetic heritage and environmental conditions, present throughout each of the stages of the illness. Current therapeutic approaches, mainly consisting of intraocular drug delivery, are only used for symptoms relief and/or to decelerate the progression of the disease. Furthermore, they are overly simplistic and ignore the complexity of the disease and the enormous differences in the symptomatology between patients. Due to the wide impact of the AMD and the up-to-date absence of clinical solutions, the development of biomaterials-based approaches for a personalized and controlled delivery of therapeutic drugs and biomolecules represents the main challenge for the defeat of this neurodegenerative disease. Here we present a critical review of the available and under development AMD therapeutic approaches, from a biomaterials and biotechnological point of view. We highlight benefits and limitations and we forecast forthcoming alternatives based on novel biomaterials and biotechnology methods. In the first part we expose the physiological and clinical aspects of the disease, focusing on the multiple factors that give origin to the disorder and highlighting the contribution of these factors to the triggering of each step of the disease. Then we analyze available and under development biomaterials-based drug-delivery devices (DDD), taking into account the anatomical and functional characteristics of the healthy and ill retinal tissue.